Botulism-like symptoms in an immunocompetent patient with Clostridium subterminale bacteremia. (2018) - Carrasquillo, Marytere; Dever, Lisa L.; Sonyey, Alexandra
Abstract: Clostridium subterminale is a low virulence species of Clostridium that is an infrequent cause of human infections. We report a case of C. subterminale bacteremia in an immunocompetent patient who developed botulism-like symptoms.